2020
DOI: 10.1186/s12905-020-01046-x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and opportunities confronting female-headed households in Iran: a qualitative study

Abstract: Background: Female-headed households are one of the most vulnerable groups of society that confront many problems and challenges. Therefore, the present study aimed to explore the challenges and opportunities confronting female-headed households in Iran. Methods: This qualitative study was conducted among female-headed households in Kermanshah, West of Iran, in 2019. The data were collected through Semi-structured interviews with 26 female-headed households who were selected by purposeful and theoretical sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 39 publications
2
47
0
Order By: Relevance
“…It has been further reconfirmed that family support is a positive and important factor affecting psychological health [34,35]. These findings are in line with the qualitative research [36] showing the problems of female-headed households have become a big threat such as role overload or poverty reproduction as well as an opportunity such as social maturity.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It has been further reconfirmed that family support is a positive and important factor affecting psychological health [34,35]. These findings are in line with the qualitative research [36] showing the problems of female-headed households have become a big threat such as role overload or poverty reproduction as well as an opportunity such as social maturity.…”
Section: Discussionsupporting
confidence: 65%
“…However, active policy support is also needed such as community resources to help prevent probable health problems in the future. In addition, their health improvement can be achieved through training and helping them to adapt to new and multifaceted roles, providing more economic support and helping them raise their social status [36].…”
Section: Discussionmentioning
confidence: 99%
“…As such, the mainstream literature on female-headed households and poverty indicates that female-headed households constitute the "poorest of the poor" (Chant, 2007;Liu & Treviño, 2017), and several other studies have shown a link between female-headed households with poverty and low socioeconomic status (Goebel et al, 2010;Javed & Asif, 2011;Montoya & Teixeira, 2017). In 2019, Lebni et al (2020) conducted a qualitative study among female-headed households in Kermanshah, West of Iran. They collected data through semi-structured interviews with female-headed households who were selected purposefully.…”
Section: Results Of Step By Step Multiple Linear Regression Analysismentioning
confidence: 99%
“…All participants provided written informed consent. The entire sample population was calculated using the theoretical saturation criteria [ 44 ]. In other words, data collection was halted when the researchers determined that more interviews and observations would not provide them with new information.…”
Section: Methodsmentioning
confidence: 99%